Systems physiology of the baroreflex during orthostatic stress: from animals to humans - Kamiya, Atsunori; Kawada, Toru; Sugimachi, Masaru (Frontiers in Physiology, 2014)
The baroreflex is a key mechanism involved in the control of arterial pressure (AP) during orthostasis in humans. However, the baroreflex is a closed-loop feedback system, from baroreceptor pressure input to systemic AP, and therefore requires open-loop experiments to identify its system characteristics. The requirement limits our ability to identify baroreflex system characteristics in humans. Open-loop research in animals has revealed dynamic and static characteristics of the two baroreflex subsystems: the neural and peripheral arcs. The neural arc, from baroreceptor pressure input to sympathetic nerve activity (SNA), has high-pass dynamic characteristics, indicating that more rapid change in input AP causes greater response in SNA. In contrast, the peripheral arc, from SNA input to systemic AP, has low-pass characteristics. Orthostasis increases the gain of the neural arc, which compensates for the lower transfer gain of the peripheral arc and in turn maintains total baroreflex function. Here, I discuss the possibility that baroreflex subsystem characteristics identified in animals can be applicable to the human sympathetic response to orthostasis, with a focus on loading speed-dependence of orthostatic sympathetic activation.